SEC5 is involved in M2 polarization of macrophages via the STAT6 pathway, and its dysfunction in decidual macrophages is associated with recurrent spontaneous abortion - Yang, Long; Zhang, Xuan; Gu, Yan; Shi, Yan; Wang, Long-Bin; Shi, Jia-Xin; Zhen, Xing-Xing; Xin, Ya-Wei; Gu, Wen-Wen; Wang, Jian (Frontiers in Cell and Developmental Biology, 2022)
Decidual macrophages (DMφs) play critical roles in the establishment of microhomeostasis at the maternal-fetal interface during pregnancy. Impaired macrophage polarization during early pregnancy is associated with recurrent spontaneous abortion (RSA). It was found in the present study that, the SEC5 expression level was significantly decreased in primary dMφs of the patients with RSA, and the down regulated SEC5 expression inhibited M2 polarization and phosphoryla-tion of STAT6, whereas its overexpression in the Mφs promoted M2 polarization and STAT6 phosphorylation in vitro. We subsequently found that SEC5 interacted with STAT6 in THP-1-derived Mφs. The abundance of phosphorylated STAT6 (pSTAT6) protein was obviously increased with a predominant distribution in the nucleus after M2 polarization of Mφs, and SEC5 protein was colocalized with pSTAT6. Moreover, a significantly reduced pSTAT6 expression level was observed in dMφs of the patients with RSA. M2 polarization of Mφs showed a stimulatory effect on the proliferation and invasion of human extravillous trophoblasts (EVTs) in vitro, and downregulated SEC5 expression in Ms could effectively reverse this effect. In the mouse model of LPS-induced early pregnancy loss, the uterine SEC5 expression level, as well as the number of M2-Mφs at the maternal-fetal interface, was significantly reduced. More interestingly, SEC5 knockout (SEC5-/+) mice were more sensitive to LPS-induced abortion. Taken together, these data indicated that, SEC5 participate in regulation of M2 polarization of Mφs by interacting with STAT6, and the decreased SEC5 expression inhibit the M2 polarization of dMφs and result in early preg-nancy loss by interfering with the physical activities of EVTs and immuno-tolerance at the ma-ternal-fetal interface.